Clinical research in Africa And Middle East: roadmap for reform and harmonisation of the regulatory framework and sustainable capacity development - Faiez Zannad; Mohamed Sobhy; Wael Almahmeed; Mohamed Balghith; Javed Butler; Souad Dziri; Sahar Ebrahim; Ashraf El Fiky; Ahmed Elshal; Ines Fradi; Ziyad Ghazzal; Chokri Jeribi; et al. (Journal of Global Health Reports)
The Middle East, Mediterranean, Africa (MEMA) region, is composed of 68 countries, totalling a population of over 1.6 billion ie, 20% of the world. It contributes little to the international effort of health knowledge production, hosting only 6% of the worldwide registered trials. Among the many weaknesses of clinical research in MEMA region is the cultural gap and lack of recognition for the need of developing a sustainable clinical research infrastructure. Very few countries have some developed capacity for research. Lack of a robust, international standards, regulatory framework is the second major hurdle. In addition there is uncertain public confidence and poor awareness of the importance and the objectives of clinical research. However, the region has a number of attractive features, such as population's size and large pool of eligible patients, least trial saturated of all regions, diversity in genetic profile, lifestyle, and eating habits, and large medication-naive patient populations.